Analysis of XYZ’s Health Product Communication Strategy in Fulfilling the Elements of the Pharmaceutical Industry Code of Conduct - Senjatiana, Ferdy; Noer, Mochammad Kresna (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the health product communication strategy implemented by Company XYZ in complying with the pharmaceutical industry's code of conduct in Indonesia. As a member of the International Pharmaceutical Manufacturers Group (IPMG), Company XYZ faces challenges in delivering ethical product messages amid strict regulations from the Indonesian Food and Drug Authority (BPOM) and IPMG’s code of ethics, which prohibits direct-to-public promotion. This research employs a qualitative approach using a descriptive case study method, involving in-depth interviews, document analysis, and observation. The findings reveal that Company XYZ applies an adaptive and ethical communication strategy through narrative approaches, selective media mapping, and active engagement in industry associations. The strategy reflects a glocal approach, where global communication policies are adjusted to local contexts. Another key finding is the practice of grey area compliance, where communication strategies technically do not violate regulations but still convey product messages implicitly. While this demonstrates the communication team’s ingenuity in navigating regulatory boundaries, it also poses potential risks of unethical communication if not properly managed. This study proposes the development of a more contextual, strategic, and regulation-compliant health product communication model, adapted from the corporate communication framework introduced by Nurlaela Arief. This model is expected to serve as a reference for communication practices in the complex and dynamic pharmaceutical industry.